Rehabilitation program for the person with fracture of the upper femur end: Case Study - Magali Palma; Helena Teixeira; Hélder Pino; João Vieira; Maria José Bule (Associação Portuguesa dos Enfermeiros de Reabilitação, 2021)
Introduction: The fracture of the upper extremity of the femur, often resulting from falls in the elderly, may require surgical intervention and lead to a deficit in the capacity for self-care, with impaired balance, walking and decreased ability to perform their daily life activities. Objective: To identify the contributions of rehabilitation nursing care to the self-care of people with fractures of the upper third of the femur. Methodology: Case study that respects the CAse REport guidelines, in which the case of a person with a fracture of the upper extremity of the femur is presented. Results: There were gains related to the prevention of respiratory and musculoskeletal complications, increased muscle strength, improved balance, functional capacity for self-care, knowledge about safety measures and adaptive techniques. A high risk of falling remained. Discussion: It is suggested a more prolonged follow-up to evaluate the gains obtained in the long term and the search for factors that may contribute to the reduction of the risk of falling. Conclusion: The intervention of the Specialist Nurse in Rehabilitation Nursing in the person with a fracture of the upper extremity of the femur is fundamental for restoring their autonomy and functional capacity.